On the possibility of Paretian liberalism: a comment - Wulf Gaertner (Theory and Decision, 2022)
In 1981, the property of self-supporting preferences was shown to be a sufficient condition to circumvent Sen's famous impossibility result on Paretian liberalism. A similar condition was proposed by Dougherty and Edward in a very recent issue of this journal. The present comment sheds light on the logical connection between these two findings.
Keywords: 300; Social choice; Individual rights exercise; The Paretian dilemma; A possibility result